Balance Scorecard Strategi Peningkatan Kinerja Organisasi - Nasir Usman (Jurnal Transformasi Administrasi, 2013)
Performance of organization is one of the factors that affect the achivement of organizational goals. The Improvement of organizational performance is affected by the strategy which is made as a procedure approach, method and ways of leadership and members of organizational in determining desicion and mechanism of the existing relationships among units within the organization. One of the strategies which are used in improving organizational performance is through balance scorecard. Balance scorecard oriented on work measurement which is seen by financialperspective,costumer,internalbusinessprocesses,learningandgrowth.